Adaptive Latent Inhibition in Associatively Responsive Optoelectronic Synapse. (25th April 2021) - Ng, Si En; Yang, Jingting; John, Rohit Abraham; Mathews, Nripan
Abstract: The association of stimuli is an important attribute in the neural basis of learning and memory. While the acquisition and extinction of association through conditioning are well emulated in artificial synaptic devices, the alteration of conditioning efficacy, which enables adaptability in learning, has yet to be demonstrated. A distinctive feature of latent inhibition is that the pre‐exposure to a neutral stimulus would suppress its subsequent associative pairing with a biologically salient counterpart. This presents an adaptive advantage in suppressing the learning efficacy of irrelevant stimuli, focusing attention only on relevant cues. Given the significant impact of the regulatory function in biological synapses, an associatively responsive optoelectronic synapse based on oxide Schottky interface capable of emulating latent inhibition is demonstrated. While optical programming based on photo‐assisted charge detrapping emulates the biologically salient stimulus, electrical modification acts as neutrally stimulating cues, capable of altering subsequent carrier recombination dynamics. The electrical–optical coupling is leveraged to implement inhibition and facilitation of synaptic plasticity. Subsequently, the adaptability in conditioning to regulate information uptake is demonstrated via latent inhibition. Distinct from conventional optoelectronic synapses, the proposed synaptic device offers significant advantages in adaptability in learning with an electrically tunable optical memory. Abstract : The association of sensory stimuli is a key principle of learning. Associative synapses capable of not only storing but also processing information are pivotal enablers of circuits that can learn. Here, a photomemristor device, capable of both volatile electrical and persistent optical switching, is designed to emulate the classical conditioning and latent inhibition paradigm.